(untitled) (International Journal of Engineering and Computer Science, 2017)
Sorting has made their importance in computing field as well as the applications we face in real life. So far many algorithms come into existence in current era. In this research paper we present a new sorting algorithms i.e. Enhanced division Selection sort. We try to enhance the performance of Selection sort by doing some modifications in the pseudo code. A comparison also has done to do analysis between existing Selection Sort and Enhanced division Selection Sort. After comparison we found that the new algorithm has produced better results and good performance during the running time.